Women Empowerment through Education in the 21st Century - Bhagyashri J Poleshi, (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
The 21st century has brought new opportunities as well as challenges for women. Globalization, digital technology, and progressive policies have opened doors for women to pursue education, careers, and leadership roles. In 2025, women empowerment and education remain central to building an inclusive and progressive society. Education is the foundation of empowerment, giving women knowledge, confidence, skills, and opportunities to participate equally in economic, social, political, and technological fields. The growth of digital learning, skill development, and global awareness has expanded opportunities, yet barriers like the digital divide, gender inequality, and patriarchal norms continue. This paper highlights how education in 2025 acts as a catalyst for gender equality, sustainable development, and social transformation. Women empowerment through education is one of the most significant factors for achieving gender equality, sustainable development, and social progress. Education gives women knowledge, skills, and confidence to participate in decision-making at household, community, and national levels. In the 21st century, women have achieved remarkable progress in education, yet challenges such as gender bias, socio-economic barriers, and cultural constraints still exist. This paper discusses the role of education in empowering women, its impact on society, and the challenges and opportunities for ensuring inclusive and equitable education for all women.
Keywords: Women Empowerment; Education; Gender Equality; Sustainable Development; Social Change